Early Life Adversity and Clinical Intimate Partner Violence in Adulthood: The Mediating Role of Interpersonal Conflict in Adolescence - Thomas, Jordan L. (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) is associated with adverse outcomes for both victims and perpetrators, though there is significant heterogeneity in manifestations of relationship violence. A growing amount of research has focused on elucidating predictors of clinical IPV?defined as severe violence involving institutional or medical intervention due to actual or potential injury?so as to better understand potential prevention and intervention targets. Early life adversity (ELA) is associated with IPV in adulthood, yet this literature focuses on discrete, retrospectively reported adversities (e.g., physical abuse and neglect) and has yet to consider clinical IPV as an outcome. Little is known about if and how broadly adverse early environments may confer risk for this specific form of relationship violence. We investigated associations between exposure to ELA prior to age five and clinical IPV victimization and perpetration by age 20 in a longitudinal, community-based sample of men and women in Australia (N = 588). Early life adversity was prospectively indexed by maternal reports of financial hardship, child chronic illness, maternal stressful life events, maternal depressive symptoms, parental discord, and parental separation. Youth interpersonal conflict life events at age 15?an interviewer-rated assessment of episodic stressors involving conflict across relationships in mid-adolescence?was tested as a potential mediator for both victims and perpetrators. Among women, ELA predicted IPV victimization and perpetration, and interpersonal conflict life events partially mediated the link between ELA and victimization, but not perpetration. Neither ELA nor interpersonal conflict life events predicted victimization or perpetration among men. Women exposed to ELA are at-risk for conflictual interpersonal relationships later in life, including violent intimate relationships, and deficits in conflict resolution skills may be one mechanism through which ELA leads to IPV victimization among this subgroup. Violence prevention and intervention efforts should target interpersonal skills, including conflict resolution, among women and girls exposed to adverse early environments.